Democratic Governance: Civil Society Participation in Migrant Worker Advocacy - Achmad Nur; Dwi Harsono (Indonesian Association for Public Administration (IAPA), 2020)
This article was (1) to examine the process of democratic governance carried out by Yogyakarta Legal Aid Institute through advocating the Erwiana case and (2) to find out the supporting and inhibiting factors in promoting democratic governance. This study is descriptive qualitative research. The informants were the director, head of the division, and members of Yogyakarta Legal Aid Institute and Erwiana as the beneficiary. Data collection techniques used non-participant observation, interviews, and documentation studies and followed with data sources triangulation to check its validity. The data analysis then applied an interactive model through data collection, data presentation, verification, and conclusions. The results showed that the Yogyakarta Legal Aid Institute's implementation of democratic governance in advocating law enforcement on the injustices experienced toward migrant workers was optimal. As an NGO, LBH has been able to bridge differences in legal policies between the two countries and efficient against diplomatic barriers. Its supporting factors are political development as mobilization and mass participation, collaboration with grassroots groups, donor support, and public policies that support case counseling. Simultaneously, the inhibiting factors are political will, intolerant group resistance, and lack of human resources.